Cities, environment & communities - Zakariya, Khalilah (Kulliyyah of Architecture and Environmental Design, IIUM, 2013)
Preface The relationships between the natural and man-made environments are among the essential components in ensuring the sustainability of a region. The interactions and process across these components operate from the regional scale, to the city scale, down to how different users inhabit and utilise the spaces. Cities, Environment and Communities is a compendium of articles that collectively look into this dynamic relationship between the city, nature and people. This book is part of the collection of undergraduate and postgraduate seminar papers (Chapter 1 to Chapter 7) that were scientifically reviewed and presented in UMRAN 2012: Green Wave Seminar, held on 3 May 2012 at Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia. Following their nature and categories, the other part of the scientifically reviewed seminar papers are compiled in another book entitled “Sustainable Approaches in the Built Environment”. The theme of the seminar, “Green Wave”, aspired to share approaches and ideas for the persisting environmental and place degradation, while at the same time to continue promoting local and global awareness towards our environment and how we occupy the spaces as users. The last three chapters are findings from three research projects that were conducted locally and internationally. Chapters 1, 2 and 3 focus on the city as an urban environment that is occupied by the urban community. In Chapter 1: ‘The Role of Urban Agriculture in Improving Green Cities: Health and Food Security’, the author examines the potential views on development of urban agriculture as an integral part of green cities towards sustainable development. Chapter 2: ‘Urban Village: A Case Study of Kampung Baru, Kuala Lumpur – Biodiversity in the Green Space’, investigated key findings in improving, preserving and maintaining the rich biodiversity between human development and conservation of green space. The case study represents the oldest urban village in Kuala Lumpur. Then going further into the utilisation of urban spaces, in Chapter 3: ‘Loose Spaces and Street Vending Activities: A Case Study in Sri Gombak, Selangor’, the authors explored how street vending activities and loose spaces could be a part of the larger urban environment by identifying the differences and similarities of spatial and behavioural patterns. Chapters 4, 5, 6 and 7 then look closer at the community of the institution and public building environment, where built and natural spaces are analysed in relationship to their immediate users. In Chapter 4: ‘Theoretical Approach in Greening the Pedestrian Movement: The Application of Crowd Simulation Model in Built Environment’, the author studied how crowd movement in stadiums can be understood to promote sustainable planning of pedestrian movements by reviewing existing body of literature and research. Then, in Chapter 5: ‘Plazas and Courtyards as Informal Spaces for the Campus Community’, attention is given to roles of open spaces in the campus as potential areas for students to conduct a range of activities, while at the same time possessing design criteria that is responsive to the environment. Chapters 6 and 7 take us to understand a natural component of the campus environment, which is the river. In Chapter 6: ‘Aesthetic Riverine Garden: Islamic Garden Design to Revitalise the River of IIUM’ the authors found that aspects of Islamic garden design is suitable to be adapted to a river development, particularly as a place to reflect, mediate and come closer to nature and one’s soul. In a different angle, authors in Chapter 7: ‘Preference for Scenic Beauty and Green Open Spaces: A Case Study of Sungai Anak Pusu, IIUM River Corridor’ discovered that the relationship and interaction between human and river can be understood from two different aspects: scenic beauty preference and users’ green space preference. The last section of the book, Chapters 8 and 9: ‘Learning through Landscape: An Early Study on the Use of Ferns as Medicinal Plants in the Maori Society in New Zealand’, explores the concept of environment and communities through an international case study on the Maori society and cultural landscape in New Zealand. The former chapter introduces us to the diversity in community landscape through a cultural ceremony, while the latter takes us into how the Maori society uses ferns in their medicinal practices. The final chapter, Chapter 10: ‘Measuring Affect and Influences of National Park to the Surrounding Residents of Kubah National Park in Sarawak, Malaysia’, analyses the contribution of the national park to its surrounding communities. Collectively, Cities, Environment and Communities offers multiple viewpoints on how planners and designers can approach these three interrelated components. The findings from these studies can be further explored and adapted to other arising urban and environmental problems. Essentially, a balance between the built, the natural and the cultural aspects of a place need to be well integrated.